Análise do processo de trabalho das equipes de saúde bucal na microrregião de sobral e sua relação com os atributos da atenção primária à saúde - Martins, Pollyanna (2012)
The objective of this study was to analyze the process of work of the Oral Health Teams (OHT), at the Primary Health Care (PHC) in 11th Region Health of Sobral city, Ceará state, Brazil, and OHT in relation to the attributes of the PHC. For data collection, questions adapted from the Assessment Instrument PHC (PCATool), professional version and subjective questions. Statistical tests analyzed the association between the variables. The method of thematic content analysis was applied to the subjective questions. The questionnaire was answered by 91 dentists and the non-response rate and refusals was 12.8%.The coordination of care and family counseling had a high overall score (> 6.6) in all population sizes. A community orientation and cultural competence scores were close to ideal. The acess and the longitudinality attribute reached low overall score (<6.6). The Access had the lowest average score in all population sizes and for all the attributes of the PHC. All types of population size had low overall score for PHC. There was a positive association between population size of cities, the presence of registration of patients, carrying out home visits and flexibility in opening hours of the OHT. The Employability, through formal links, presented positive association with length of stay on the same team, and negative association with population size of cities.The graduate in Family Health was positively associated with the working time of the dentist in the PHC. The demand schedule was more present in the OHT at cities above 20,000 inhabitants.The groups prioritized between the OHT, which have some kind of demand schedule, were the pregnant women, children, adults and elderlies. Most of the OHT (86%) perform basic clinical procedures, however, carrying out other activities such as home visits and installation of complete dentures are in early stages of deployment. ensure care for patients seeking health services and to priorizite groups for Oral attention are challenges for OHT. The practices changing in the work process of the OHT are in incipient process, however, it was found that a greater systematization of these actions in big cities.The use of PCATool allowed opportunity to examine the presence and extent of the attributes of the PHC in the working process of the OHT, and as a method for obtaining information on the direction and performance of oral health services in the PHC.